The IL-17 Family of Cytokines in Psoriasis: IL-17A and Beyond - Brembilla, Nicolo Costantino; Senra, Luisa; Boehncke, Wolf-Henning (Frontiers in Immunology, 2018)
Psoriasis is a frequent chronic inflammatory skin disease, nowadays considered a major global health problem. Several new drugs, targeting the IL-23/IL-17A pathway, have been recently licensed or are in clinical development. These therapies represent a major improvement of the way in which psoriasis is managed, since they show an unprecedented efficacy on skin symptoms of psoriasis. This has been made possible thanks to an increasingly more accurate pathogenic view of psoriasis. Today, the belief that Th17 cells mediate psoriasis is moving to the concept of psoriasis as an IL-17A-driven disease. New questions arise at the horizon, given that IL-17A is part of a newly described family of cytokines, which has five distinct homologous: IL-17B, IL-17C, IL-17D, IL-17E, also known as IL-25, and IL-17F. IL-17 family cytokines elicit similar effects in target cells, but simultaneously trigger different and sometimes opposite functions in a tissue-specific manner. This is complicated by the fact that IL-17 cytokines show a high capacity of synergisms with other inflammatory stimuli. In this review, we will summarize the current knowledge around the cytokines belonging to the IL-17 family in relation to skin inflammation in general and psoriasis in particular, and discuss possible clinical implications. A comprehensive understanding of the different roles played by the IL-17 cytokines is crucial to appreciate current and developing therapies, and to allow an effective pathogenesis- and mechanism-driven drug design